The Cambridge companion to Machiavelli - Najemy, John M. (Cambridge ; New York : Cambridge University Press, 2010)
"Niccolo Machiavelli (1469-1527) is the most famous and controversial figure in the history of political thought and one of the iconic names of the Renaissance. The Cambridge Companion to Machiavelli brings together sixteen original essays by leading experts, covering his life, his career in Florentine government, his reaction to the dramatic changes that affected Florence and Italy in his lifetime, and the most prominent themes of his thought, including the founding, evolution, and corruption of republics and principalities, class conflict, liberty, arms, religion, ethics, rhetoric, gender, and the Renaissance dialogue with antiquity. In his own time Machiavelli was recognized as an original thinker who provocatively challenged conventional wisdom."--Provided by publisher.
Niccolò Machiavelli : a portrait / James B. Atkinson -- Machiavelli in the chancery / Robert Black -- Machiavelli, Piero Soderini, and the republic of 1494-1512 / Roslyn Pesman -- Machiavelli and the Medici / Humfrey Butters -- Machiavelli's Prince in the epic tradition / Wayne A. Rebhorn -- Society, class, and state in Machiavelli's Discourses on Livy / John M. Najemy -- Machiavelli's military project and the Art of war / Mikael Hörnqvist -- Machiavelli's Florentine histoires / Anna Maria Cabrini -- Machiavelli and Rome : the republic as ideal and as history / J.G.A. Pocock -- Philosophy and religion in Machiavelli / Alison Brown -- Rhetoric and ethics in Machiavelli / Virginia Cox -- Machiavelli and poetry / Albert Russell Ascoli & Angela Matilde Capodivacca -- Comedian, tragedian : Machiavelli and traditions of Renaissance theater / Ronald L. Martinez -- Machiavelli and gender / Barbara Spackman -- Machiavelli's afterlife and reputation to the eighteenth century / Victoria Kahn -- Machiavelli in political thought from the age of revolutions to the present / Jérémie Barthas.
Bibliografske bilješke na kraju svakog poglavlja.
Kazalo
Keywords: Machiavelli, Niccolò -- filozofija